(untitled) (Revista Española de Fisiología, 1991)
Ovariectomized Wistar rats received bilateral electrolytic (n = 24) or sham (n = 11) lesion of the nucleus accumbens. Following priming with estradiol benzoate (25 micrograms/rat) and progesterone (0.5 mg/rat) they were tested for sexual behavior with a stud male. Tests were carried out once prior to operation and twice postoperatively. Both lordosis and rejection behaviors as responses to male mount attempts were evaluated for each session. Proceptive patterns (hopping, darting and presenting) were also recorded. Females with accumbens lesion did not differ from control animals either with regard to lordosis or to soliciting behaviors. On the contrary, the lesioned group showed a statistically significant increase in rejection behavior in both postoperative sessions (p less than 0.05 and p less than 0.002). In conclusion, nucleus accumbens lesion dissociated the normal correlation between lordosis and rejection responses to male mount attempts without affecting soliciting behaviors. This finding is thought to be related to the hyperreactivity produced by nucleus accumbens lesion.